Stabilization of the Cauchy problem for integro-differential equations - Kengne, E.; Tayou, Simo J. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
In the present paper, we obtain a criterion for the stabilization of the Cauchy problem for an integro-differential equation in the class of functions of polynomial growth γ ≥ 0.